Покращення якості агломерату шляхом удосконалення способу підготовки шихти - Бочка, В.В.; Сова, А.В.; Двоєглазова, А.В. (Physico-technological Institute of Metals and Alloys, 2023)
In order to obtain high-quality agglomerate stabilized in terms of grain size and strength, it is necessary to form a block structure with an optimal mineralogical composition of the interblock bond, which consists of calcium ferrites and iron-calcium olivines. An important technological step in obtaining high-quality agglomerate is the preparation of sinter charge for sintering. One of the ways to improve the preparation of the sinter charge is the use of separate pelletizing of its components. It creates the ability to control the processes of formation and growth of crude granules, as well as the formation of their chemical composition and properties. To create the conditions for the formation of agglomerate of a given composition and properties, a study of the characteristics of the preparation of the charge with the use of pre-prepared composites based on concentrate was carried out. Compositions were formed in such a way as to promote the emergence and growth of granules, and even distribution of the components of the charge in them. The results of the study showed that the pelletizing of the charge using pre-prepared composites leads to: a significant reduction in the fraction amount of 0–1 mm; an increase in the equivalent diameter of the granules; reduction of the mean square deviation and coefficient of variation, indicating a more homogeneous granulometric composition of crude granules. At the same time, in the crude granules, the content of the fraction +10 mm is significantly increased, which negatively affects the sintering process of the agglomerate. The main reason for this may be the presence in the charge of large particles of ore and back, which significantly affect the processes of formation and growth of granules. It has been experimentally proved that the best results are achieved by using a pre-prepared composite (basically 0.95–1.0 units) from concentrate, ore, 0–3 mm in size, lime and limestone, while the basicity of the residual charge is – 1.65-1.7 units. This creates the conditions for the formation of a strong interlacing bond, consisting mainly of olivines of low basicity and ferrites. In accordance with the technological scheme of preparation of the charge, initially there is a dosage, mixing and pelletizing of the proposed composite, while the residual charge is dosed and mixed separately. After this, there is a common granulation of the composite and the residual charge in the drum granulator. Solid fuel, 0–7 mm in size, is fed to the charge at the end of the granulation.